Optimizing Legal Protection of Communal Intellectual Property for Regional Specialty Products to Promote Local Economic Growth - Muhammad Satria Akbar; Ravie Surya Justico; Rayhan Ade Dwiyana; Ikhwan Aulia Fatahillah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the effectiveness of communal intellectual property protection in safeguarding regional specialty products and promoting local economic growth in Indonesia through a normative legal research approach. The analysis is based on statutory and conceptual approaches using primary legal sources, including Law Number 20 of 2016, Law Number 28 of 2014, Government Regulation Number 56 of 2022, and Ministerial Regulation Number 13 of 2017, complemented by scholarly literature on intellectual property governance and regional development. The findings indicate that Indonesia has established a relatively comprehensive legal framework for protecting geographical indications, traditional knowledge, and traditional cultural expressions. Despite this regulatory foundation, implementation remains constrained by documentation deficiencies, fragmented institutional authority, limited community participation, and uneven regional administrative capacity. The study further demonstrates that effective communal intellectual property protection contributes to product differentiation, market reputation, community empowerment, regional competitiveness, and sustainable economic development. Legal protection functions not only as a mechanism for cultural preservation but also as a strategic development instrument. Strengthening institutional coordination, improving registration systems, and expanding community based governance are essential to optimize the developmental benefits of communal intellectual property protection within Indonesia's regional economic landscape.